An Implementation of a Single Board Computer as a Home Vital Sign Monitoring System Using a Raspberry-Pi - Susana, Ernia; Handayani, Indah Nursyamsi; Komarudin, Agus (International Journal of Electrical, Computer, and Biomedical Engineering, 2023)
Health monitoring and related technologies are a growing area of research. The embedded technology enables designing and manufacturing a single board computer (SBC) based vital signs monitoring system prototype. This study aims to develop and test an equipped with a monitor of vital signs, including electrocardiogram, heart rate (HR), respiratory rate (RR), and body temperature. The results showed that the prototype could work well, all parameters could be displayed on the 7" TFT touch screen, and the operation used Bahasa instructions. Qualitative test results show all the parts and the function is working correctly. Quantitative heart rate test results show an accuracy of 95% with a range of 30-200 bpm and 93% for the temperature parameter.